2022
DOI: 10.3390/su141710884
|View full text |Cite
|
Sign up to set email alerts
|

A DEMATEL Framework for Modeling Cause-and-Effect Relationships of Inbound Contamination in Single-Stream Recycling Programs

Abstract: Material Recovery Facilities (MRFs) are the foundation of United States recycling programs. MRFs collect recyclable materials from end users for export to be processed abroad or to sell to mills for further refinement and reuse. The most popular type of recycling collection in the United States is Single-Stream Recycling (SSR). Numerous studies have validated the program’s popularity and consumer acceptance. In contrast to other recycling plans, SSR’s favored status rests on its minimal consumer burden, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Community awareness is a critical factor for increasing both the quality and quantity of the plastic waste collected via a SWC system. This is supported by the study presented in [41]. The study proposed a technique which considers a panel of experts to identify contamination causes in commingled SWC systems.…”
Section: Community Awarenessmentioning
confidence: 81%
“…Community awareness is a critical factor for increasing both the quality and quantity of the plastic waste collected via a SWC system. This is supported by the study presented in [41]. The study proposed a technique which considers a panel of experts to identify contamination causes in commingled SWC systems.…”
Section: Community Awarenessmentioning
confidence: 81%
“…There is also an increased chance that glass will become broken during the recycling operations [8]. The level of recycling education/awareness plays a role in controlling the contamination of wastes for SSR [9,10]. Higher levels of contamination reduce the resale price of the repurposed materials due to poor quality [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the two methods are used widely these days, a comparison of sustainability (environmental, economic, and social) performance between the two has rarely been studied. There are more often studies and research found regarding only one of the sustainability aspects [10,[14][15][16][17][18][19][20][21][22][23][24]. Wang assessed participation and recycling rates after switching to a single-stream collection system but lacked an environmental or economic evaluation [3,25] and focused on the cost-benefit analysis, with a small evaluation of the social costs of switching to an automated collection with single-stream [3,26].…”
Section: Literature Reviewmentioning
confidence: 99%